Agricultura urbana e periurbana: Conceito, experiências nacionais e internacionais, desafios e o programa nacional de agricultura urbana e periurbana - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
Agriculture constitutes an activity intrinsically linked, in the collective imagination, to the rural world. Such economic activities are also, however, carried out in cities, and their mediations. This study aims to provide a current overview of AUP in Brazil and evaluate the challenges inherent to the activity, including the role that the National Urban and Peri-Urban Agriculture Program can have in promoting its development. The relationship between advantages and disadvantages of the practice in Brazilian cities will depend on some factors, including the incorporation of the theme within the scope of urban planning and the existence of specific regulations on various issues related to the modus operandi of AUP in Brazil. The analysis of the master plans of Brazilian capitals suggests that the AUP needs to be incorporated into Brazilian urban planning. The promotion of AUP and its expansion also depends on the existence of a whole series of support elements (credit, credit assistance, etc.). The creation and focus of specific public policies for urban farmers will depend on greater knowledge of the reality of these people and the production systems used by them in their AUP activities.
Keywords: Q1; Q18; 330; agriculture; urban agriculture; urban planning